The Informavore Shopper: Analysis of Information Foraging, System Design, and Purchasing Behavior in Online Retail Stores - HONG, Jeff Min Teck (Institutional Knowledge at Singapore Management University, 2013)
Global online retail sales are on the rise and are predicted to experience a double digit growth annually over the next three years. Given little marginal cost involved in adding new products and brands to their catalogues, online retailers tend to increase product and brand offerings to increase sales by selling products that could not have been sold due to space constraints in physical stores. Frank Urbanowski, Director of MIT Press, attributed the 12% increase in sales of backlist titles directly to increased accessibility to these titles through the Internet. For consumers, the ability to buy products that they would not have otherwise bought increases their consumer surplus. Despite preferring a large assortment of products in online retail stores due to product variety and diversity in brand choices, this poses a problem to consumers as the number of alternatives and attributes reduces their confidence in the selection of a product to purchase; product comparison and evaluation also becomes a difficult task. Thus, an online retail store that does not facilitate easy product information search, comparison, and evaluation would cause consumers to make poor purchase decisions. In this thesis, I investigate how the design parameters of online stores such as the presentation of product information, product comparisons, consumer reviews, and recommendations influence consumers’ information seeking and decision-making processes. Specifically, the objectives of this thesis are to learn the individual and joints effects of such design parameters on the effort that consumers expend in the shopping process, quality of their purchase decisions, and their satisfaction with the shopping experience. A controlled experiment was conducted online using six variants of an online retail store to understand the effects of such design features. While the result was modest, the study found that presentation of information that allows consumers to have a preview of the subsequent page after clicking on a link has moderate effects on consumers' physical and cognitive effort in seeking product information, the purchase decision they made, and their satisfaction with an online store.